How Access to Urban Potable Water and Sewerage Connections Affects Child Mortality - Shi, Anqing (World Bank, Washington, DC, 2014)
Using a city-level database of global Urban Indicators, the author finds that: 1) Improved access to urban potable water and sewerage connections is consistently associated with low child mortality. 2) Government involvement in providing water services, especially locally, significantly reduces child mortality. 3) Private or parastatal participation in providing sewerage connections is associated with low child mortality. $) Rapid urban growth and high levels of poverty within the city are correlated with high child mortality.